RISE-SSc: Riociguat in diffuse cutaneous systemic sclerosis. (January 2017) - Distler, Oliver; Pope, Janet; Denton, Chris; Allanore, Yannick; Matucci-Cerinic, Marco; de Oliveira Pena, Janethe; Khanna, Dinesh
Abstract: RISE-SSc is a randomized, double-blind, placebo-controlled phase 2 study investigating the efficacy and safety of riociguat in patients with diffuse cutaneous systemic sclerosis (dcSSc). Based on positive results from riociguat trials in patients with pulmonary hypertension and chronic thromboembolic pulmonary hypertension in combination with the known antiproliferative and antifibrotic effects seen in animal models, patients with SSc may benefit from treatment with riociguat. Patients with SSc meeting the ACR/EULAR systemic sclerosis classification criteria with diffuse cutaneous SSc (dcSSc) subset per LeRoy criteria, and a disease duration of less than or equal to 18 months will be randomized to placebo or riociguat 0.5 mg (up-titrated to a maximum dose of 2.5 mg TID over 10 weeks) and maintained on therapy for a total of 52 weeks. During the first 10 weeks of the long-term extension phase, placebo subjects will be up-titrated on riociguat, and all patients will be followed for up to 6 years. The primary endpoint of change in modified Rodnan skin score (mRSS) from baseline will be assessed at 52 weeks, as will be secondary endpoints such as mRSS progression and regression rates, patient quality of life, digital ulcer burden, and change in forced vital capacity and carbon monoxide diffusing capacity. This review will further define the clinical rationale for the use of riociguat in the treatment of SSc and provide details on study protocol, design, and outcome reporting. Trial registration: Clinicaltrials.gov identifier:NCT02283762 . Highlights: RISE-SSc is investigating riociguat for the treatment of dcSSc. RISE-SSc is a randomized, double-blind, placebo-controlled phase 2 study. Animal models have shown antiproliferative and antifibrotic effects. Based on preclinical results, SSc patients may benefit from riociguat.